Mortality rate of patients with cystic fibrosis on the waiting list and within one year after lung transplantation: a survey of Italian CF centers - Beatrice Borchi; Marisol Barao Ocampo; Giuseppe Cimino; Giovanna Pizzamiglio; Silvia Bresci; Cesare Braggion; the Italian Cystic Fibrosis Lung Transplantation Group (BMC, 2018)
Abstract Background Cystic Fibrosis (CF) Centers are involved in the decisions regarding the eligibility of CF patients with end-stage lung disease and timing for inclusion on waiting lists (WL) for lung transplantation (LT). There are currently no data on the mortality rates of Italian CF patients on WL and during the first year after LT and we aimed to assess these outcomes by surveying the CF Centers. Methods A survey was sent to Italian CF Centers which were requested to report the age at which all CF subjects included on the WL between 2010 and 2014 were included on the list, admitted to either standard or urgent LT, or had died either while on the WL or within the first 3 and 12 months after LT. All outcomes were recorded by December 31, 2015. Results Two hundred fifty-nine CF subjects were included on the WL during the 5-year study period. The mortality rate during the WL was 19.3% and was not associated with sex, age at inclusion on the WL or standard or urgent access to LT. 159 (61.4%) subjects underwent LT, 46 (28.9%) with urgent procedure. Deaths within the first 3 and 12 months after LT were significantly more prevalent in individuals who underwent urgent LT compared to those with standard LT (p < 0.01). Conclusions The mortality of Italian CF patients, included in our survey, was about twice that reported by the National Transplant Center for all LT indications, including CF, during the same time period and despite the introduction of urgent LT. The latter was associated with an unfavorable early outcome compared to standard LT.